Peran Ayah Dalam Pendidikan Anak - Muryaningsih, Sri; Fauziyah, Puji Yanti (LPPM Institut Pendidikan Nusantara Global, 2024)
Fathers have a role in the family, including children. This study aims to describe the role of fathers in children's education. This research is descriptive in nature by distributing questionnaires in the form of Google Forms. The results of this study show 93.8% stated that fathers are involved in children's education. Fathers can perform the role of fatherhood in the family well if they feel happy to be a father. Fathers have a role that is no less important than mothers. Physical involvement of fathers when children eat, do homework or play activities with children improves children's cognitive, social, and creative aspects. Self-development of knowledge about parenting is done by fathers by following their instincts, sharing experiences with friends, reading books, and participating in parenting activities.